(untitled) (Eurasian Medical Research Periodical, 2022)
Health is key to the future of humanity. The World Health Organization (WHO) has developed a program to "promote health, keep the world safe and reach vulnerable populations with services." The program puts forward new targets to be achieved by 2023: ensure health coverage for the entire population at all ages; ensure improved health and well-being.In the world, the priority direction of medicine in the 21st century is the implementation of the national project “Healthcare. The purpose of this project is to preserve and strengthen the health of the population around the world through the formation of a healthy lifestyle and increasing the availability and quality of medical care [8, 2]. For the implementation of the project, a patient-centered health care model (People-Centered Health Care) was proposed